Analisis Komparasi Problem Based Learning Dengan Team Assisted Individualization Pada Penguasaan Kompetensi “Mekanisme Katup & Sistem Bahan Bakar” Kelas XI SMK - Holis Harifi; Djoko Adi Walujo; Sugito (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
Vocational school as a vocational school is different from other public high schools. Put more emphasis on competence or expertise. Monotonous learning is not varied, boring and is more centered on the teacher, causing ineffective and unpleasant. This study uses a Class Action Research (CAR) approach aimed to find out how the comparative analysis of PBL and TAI is effective in mastering the competence of "Mentup Simbahkar" valve mechanism and fuel system acronyms on Class IX Motorcycle Engine Maintenance. Based on the results of data processing can be seen: (1). Positive activity in cycle I was 61%, cycle II was 76%, and cycle III was 84%, while negative activity in cycle I was 30%, cycle II was 10%, and cycle III was 10%; (2). The average class in cycle I was 71, cycle II was 81, and cycle III was 88, (3). Mastery learning of students in the first cycle of 28.5%, the second cycle of 100%, and the third cycle of 100%.